AHP-Based Platform Selection For Zakat Management System At Rumah Amal ULM - Hafidz, Muhammad Meidy Nur; Mutmainah, Mutmainah; Lestari, Haifa; Dima, Utama Ahmed (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The improvement of information technology and the COVID-19 pandemic have triggered digitalization across all industry sectors, including zakat institutions. However, various constraints including resource considerations remain a decisive aspect impeding digital adoption in zakat management processes. While several studies on zakat management information system design have been conducted, none specifically elaborate on systematic decision-making framework for platform selection in zakat management digitalization. This research seeks to fill this gap by investigating the use of Analytical Hierarchy Process (AHP) to identify dominant criteria in platform selection decision-making for zakat digitalization at Rumah Amal ULM (RAUL) and to retrospectively analyze their platform choice against five alternative platforms using seven evaluation criteria. RAUL was selected as a case study because it is a newly established zakat institution that had already implemented a low-code platform using Google Sheets with Apps Script prior to systematic evaluation. Data were collected through interviews with RAUL leadership. The analysis results show that the low-code platform emerged as the most suitable choice, confirming RAUL’s original platform selection decision. The study also reveals that cost and accessibility emerge as nearly equally dominant criteria, contributing 27.5% and 27.3% respectively to the decision-making process, while technical considerations such as IT infrastructure and technical skill serve as secondary factors. These findings validate RAUL's initial decision while offering a structured decision-making framework that provides practical guidance for similar newly established institutions to decide which platform is more suitable to support their digital transformation processes.